2021
DOI: 10.1038/s41598-021-01233-2
|View full text |Cite
|
Sign up to set email alerts
|

U.S. national, regional, and state-specific socioeconomic factors correlate with child and adolescent ADHD diagnoses pre-COVID-19 pandemic

Abstract: Attention-deficit/hyperactivity disorder (ADHD), the most diagnosed emerging neurodevelopmental disorder in children, is a growing health crisis in the United States. Due to the potential increase in ADHD severity during and post the COVID-19 pandemic, we analyzed recent national and two state-specific ADHD data distribution among U.S. children and adolescents by investigating a broad range of socioeconomic status (SES) factors. Child and adolescent ADHD diagnosis and treatment data were parent-reported via Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 67 publications
4
14
0
1
Order By: Relevance
“…Previous studies using data from the National Health Interview Survey (NHIS) by the CDC found that from 1997-2016, weighted prevalence of ADHD diagnosis was highest in the Northeast (10.8-13.6%, 95 CI) and lowest in the West (6.1-7.8%, 95CI) [22]. This is consistent with other findings in which highest rates of ADHD diagnosis and medication use in children aged 3-17 years old for 2018-2019 were highest in Southern regions (10.97% and 7.52%, respectively) and lowest in Western regions (7.46% and 4.14%, respectively) [23].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies using data from the National Health Interview Survey (NHIS) by the CDC found that from 1997-2016, weighted prevalence of ADHD diagnosis was highest in the Northeast (10.8-13.6%, 95 CI) and lowest in the West (6.1-7.8%, 95CI) [22]. This is consistent with other findings in which highest rates of ADHD diagnosis and medication use in children aged 3-17 years old for 2018-2019 were highest in Southern regions (10.97% and 7.52%, respectively) and lowest in Western regions (7.46% and 4.14%, respectively) [23].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous examinations of state-level estimates for ADHD diagnosis and treatment (Blue Cross Blue Shield, 2019; Board et al, 2020;Bozinovic et al, 2021;Centers for Disease Control and Prevention, 2010;McDonald & Jalbert, 2013;Piper et al, 2018;Visser et al, 2014Visser et al, , 2015Visser et al, , 2016, data from the 2016 to 2019 NSCH suggests that there is substantial variation in state-level prevalence of diagnosed ADHD and associated treatment among children and adolescents aged 3 to 17 years. The percentage of children who ever received an ADHD diagnosis was more than twice as high in the states with the highest prevalence (Louisiana, Mississippi, and West Virginia) than the state with the lowest prevalence (California); most states with high ever diagnosed and current ADHD prevalence estimates were in the South.…”
Section: Discussionsupporting
confidence: 77%
“…A number of factors might contribute to the observed variation in ADHD diagnosis and treatment estimates across states. First, differences have been previously documented in the diagnosis and treatment of ADHD by demographic subgroups, such as those based on race/ethnicity or poverty status (Bozinovic et al, 2021; Danielson et al, 2018; Visser et al, 2014), and differences in state-level demographics may be driving the differences in state-level rates of ADHD diagnosis and treatment. State-level educational or health care system policies could also affect the diagnostic and treatment practices for ADHD in a given state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention deficit hyperactivity disorder (ADHD) is a prevalent, impairing condition that is frequently comorbid with other psychiatric disorders and creates a substantial burden for the individual, their family, and the community ( 1 ). Positive correlations between ADHD diagnosis and unsafe school, unsafe neighborhood, and economic hardship are evident in a recent United States national research ( 2 ). Pharmacological treatment is part of the comprehensive multimodal evidence-based strategy to achieve adequate control of core ADHD symptoms and comorbid conditions, minimizing functional impairments and improving quality of life ( 3 ).…”
Section: Introductionmentioning
confidence: 99%